2009
DOI: 10.1080/10615800902785608
|View full text |Cite
|
Sign up to set email alerts
|

The durability of beneficial health effects associated with expressive writing

Abstract: This study examined the durability of benefits associated with expressive writing. Sixty-eight college undergraduates completed measures of physical and psychological health at the beginning of their first year and were then randomized to either an expressive writing or a control writing condition. Changes in physical health, psychological health (i.e., depression, stress, and anxiety), and academic performance were assessed two, four, and six months later. Findings indicated that participants assigned to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 56 publications
(91 reference statements)
0
8
0
1
Order By: Relevance
“…Regarding the present research, it may be that the short period of time (one month) between writing and follow-up were not of adequate length for differences in University Health Center visits to emerge. A recent expressive writing study with college students, however, found no changes in physical health and stress and anxiety symptoms at 2, 4, and 6-month follow-ups (Sloan, Feinstein, & Marx, in press). Among healthy young adults, there may be little room for improvement in health outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the present research, it may be that the short period of time (one month) between writing and follow-up were not of adequate length for differences in University Health Center visits to emerge. A recent expressive writing study with college students, however, found no changes in physical health and stress and anxiety symptoms at 2, 4, and 6-month follow-ups (Sloan, Feinstein, & Marx, in press). Among healthy young adults, there may be little room for improvement in health outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…Bu noktadan hareketle yazmaya ilgisi olan öğrencilerin yazma sürecinde pek kaygılanmadıkları sonucuna varılabilir. Bazı araştırmalarda (DeSalvo, 1999;Johnson, 2000;Nye, 1997;Sloan, Feinstein ve Marx, 2009) yazmanın insanı kaygılandırmaktan öte duygusal rahatlama sağladığı üzerinde durulmaktadır. Bu araştırmada da günlük, şiir ve öykü yazan öğrencilerin yazma kaygılarının düşük olması yanında duygusal rahatlama amacıyla yazmaya yöneldikleri düşünülmektedir.…”
Section: Discussionunclassified
“…To understand the process through which changes take place, it would have been useful to check the eff ectiveness or ineff ectiveness of a writing intervention after intermediate times. Although most of the studies use only one follow-up assessment ( Sloan, Feinstein, & Marx, 2009 ), this procedure did not allow the authors to evaluate the process through which the modifi cation of symptoms took place, along with possible variation in patterns of symptoms. In particular, intermediate follow-ups could have provided more information to understand the reasons of the lack of eff ectiveness of the expressive writing on intrusive PTS and cognitive depression symptoms.…”
Section: Limitations and Strengthsmentioning
confidence: 99%